Förskolans utvecklingssamtal: Om motstridiga logiker i ett institutionaliserat möte - Lindqvist, Beatriz (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2019)
The article discusses how conflicting logics emanated from different discourses are articulated in parent–teacher conferences in a Swedish preschool. Preschool teachers ’reporting of collective learning processes is interrupted by parents’ demands for information about their child’s individual performance. When parents act as customers in the pre-school meeting, pedagogical matters can sometimes capitulate for the preschool’s need to assert itself in a market. The educators consistently express that the ambition is to fulfil educational goals and promote the children’s development and learning. However, in the meeting with parents, they may be required to answer questions about children’s individual psychological development that actualize a parallel market logic that affects the teachers’ ability of presenting their work consistently as they try to reconcile contradictions inherent to the discourses intersecting preschool as institution.